Rheological Properties in Aqueous Solution for Hydrophobically Modified Polyacrylamides Prepared in Inverse Emulsion Polymerization - Shirley Carro; Valeria J. Gonzalez-Coronel; Jorge Castillo-Tejas; Hortensia Maldonado-Textle; Nancy Tepale (International Journal of Polymer Science)
Inverse emulsion polymerization technique was employed to synthesize hydrophobically modified polyacrylamide polymers with hydrophobe contents near to feed composition. Three different structures were obtained: multisticker, telechelic, and combined. N-Dimethyl-acrylamide (DMAM), n-dodecylacrylamide (DAM), and n-hexadecylacrylamide (HDAM) were used as hydrophobic comonomers. The effect of the hydrophobe length of comonomer, the initial monomer, and surfactant concentrations on shear viscosity was studied. Results show that the molecular weight of copolymer increases with initial monomer concentration and by increasing emulsifier concentration it remained almost constant. Shear viscosity measurements results show that the length of the hydrophobic comonomer augments the hydrophobic interactions causing an increase in viscosity and that the polymer thickening ability is higher for combined polymers.